Impact of the time of initiation and line of biologic therapy on the retention rate of secukinumab in axial spondyloarthritis (axSpA): data from the French multicentre retrospective FORSYA study - Maxime Dougados; Pascal Claudepierre; Philippe Goupille; Alain Saraux; Anne Tournadre; Daniel Wendling; Cédric Lukas; Adeline Ryussen-Witrand; Emilie Desfleurs; Audrey Lardy-Cleaud (RMD Open)
Objective To compare the 1-year retention rate of secukinumab in axial spondyloarthritis (axSpA) and its predisposing factors with regard to its time of initiation (eg, right after or remotely from its launch).Methods Study design: Retrospective multicentre French study of patients with axSpA. Study periods: Two cohorts were evaluated regarding the time of initiation of secukinumab: cohort 1 (C1)—between 16 August 2016 and 31 August 2018—and cohort 2 (C2)—between 1 September 2018 and 13 November 2020. Statistical analysis: The 1-year retention rate of secukinumab was estimated using the Kaplan-Meier method, and the log-rank test was used to compare the retention curves of the two cohorts. Preselected factors (eg, disease characterristics, line and time of secukinumab initiation) of secukinumab retention at 1 year were analysed by univariate and multivariate Cox model regression.Results In total, 906 patients in C1 and 758 in C2 from 50 centres were included in the analysis. The 1-year retention rate was better in C2 (64% (61%–68%)) vs C1 (59% (55%–62%)) (HR=1.19 (1.02–1.39); p=0.0297). In the multivariate analysis, the line of biologic therapy was the single predictive factor of the 1-year retention rate of secukinumab picked up in both cohorts, with a better retention rate when prescribed as first-line biologic therapy.Conclusion The better secukinumab retention rate remotely from its launch is explained by its use at an earlier stage of the disease, suggesting a change in the behaviour of prescribing physicians. Our results emphasise the relevance of iterative evaluations of routine care treatments.